Edukasi Kader tentang Perawatan Payudara dan Teknik Menyusui di Wilayah Kerja Puskesmas Cileunyi Kabupaten Bandung - Diana Ulfah; Yani Marlina; Tri Nur Jayanti; Ade Iwan Mutiudin; Roganda Situmorang (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2024)
Breast milk is the best food for babies because it has benefits. Babies who are not exclusively breastfed have been more susceptible to infections compared to babies who are exclusively breastfed. However, the benefits of breast milk do not necessarily mean that all mothers are providing breast milk as recommended. This can be caused by problems during breastfeeding, such as sore nipples, tenderness, swelling, mastitis, and even breast abscess. Therefore, breast care and breastfeeding training must be carried out so mothers avoid breastfeeding problems. Educational activities in this activity were conducted at Posyandu Mulus Rahayu 22, attended by 14 cadres, and Posyandu Shofa 11 A, B, C by 11 cadres. Education is carried out using lectures, demonstrations, and question-and-answer methods, such as PowerPoint, leaflets, and teaching aids. Pre-tests and post-tests were carried out to evaluate participants. The evaluation results showed increased participants' knowledge from an average of 6.44 at the pre-test to 7.6 at the post-test. Education is an important step that needs to be taken to increase knowledge. It is hoped that cadres who have taken part in this activity can convey information to mothers around them so that they avoid breastfeeding problems.